x(x-4)+56=x*x

Simple and best practice solution for x(x-4)+56=x*x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-4)+56=x*x equation:


Simplifying
x(x + -4) + 56 = x * x

Reorder the terms:
x(-4 + x) + 56 = x * x
(-4 * x + x * x) + 56 = x * x
(-4x + x2) + 56 = x * x

Reorder the terms:
56 + -4x + x2 = x * x

Multiply x * x
56 + -4x + x2 = x2

Add '-1x2' to each side of the equation.
56 + -4x + x2 + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
56 + -4x + 0 = x2 + -1x2
56 + -4x = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
56 + -4x = 0

Solving
56 + -4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + -4x = 0 + -56

Combine like terms: 56 + -56 = 0
0 + -4x = 0 + -56
-4x = 0 + -56

Combine like terms: 0 + -56 = -56
-4x = -56

Divide each side by '-4'.
x = 14

Simplifying
x = 14

See similar equations:

| 8x+2=3x-2 | | -9x+11=2x+11 | | 7e+10=4e+28 | | 6x^3-6x+1=0 | | -7x+1=-13 | | Y=3.5 | | 8h+9=3h+54 | | 0.125f=0.1875 | | 3x+1.2=3.9 | | (-2)-(-6)-4= | | 4v+7=2v+15 | | 5x+5=(x-1) | | 2+2=7-3 | | 4-(8+2n)=-2(n+2) | | 9x^2-79x+56=0 | | -8x+24=0 | | 25x+5x-15=0 | | 9x-11=4x+6+5x+5 | | 9(m+2)+1=19+9m | | 5t+10=2t+31 | | 2x+4y+7=0 | | 21+2w=p | | 2x-2x+2=0 | | -2-3y=22 | | 5x=21+2a | | -x+4x=0 | | 3v+10=31 | | 4g+9=2g+17 | | Y=(-x)+8 | | -4x-2x-6=0 | | 2x+4=100000 | | 443x+8=11 |

Equations solver categories